Patient experiences with public hospital care: first benchmark survey in Hong Kong. - Wong, E; Coulter, A; Cheung, A; Yam, C; Yeoh, E; Griffiths, S (2012)
OBJECTIVE. To measure patient satisfaction in relation to in-patient experience in public hospitals. DESIGN. Cross-sectional study. SETTING. Twenty-five selected Hospital Authority acute and convalescence hospitals in Hong Kong. PARTICIPANTS. Eligible patients discharged between 15 June and 27 September 2010 from the selected Hospital Authority public hospitals. MAIN OUTCOME MEASURES. A total of 54 items were used to measure patient experience on aspects of hospital care. They included the process of admission to hospital, staying in the hospital and ward (environment, food and facilities; hospital staff; patient care and treatment), the process of leaving hospital, and the overall impression of hospital care. Free-text comments from respondents were also recorded. RESULTS. A total of 5030 patients were successfully interviewed, amounting to a response rate of 52%. The findings showed that 80% (confidence interval, 79-81%) of patients rated the care they received in hospital as good or better. However, there were a few areas where performance was relatively low, including waiting time for a ward bed for accident and emergency cases, food quality, infection control, information provided about their condition/treatment, seeking patient input about their opinions and quality of care, and patient engagement in the decisions about their treatment and care, as well as the discharge process. CONCLUSIONS. This patient experience survey used a validated instrument (Hong Kong Inpatient Experience Questionnaire) to provide important insights to executives and health care professionals on their care to patients and to identify areas for improvement in public hospitals. Further surveys should be carried out to monitor changes in patient experience and satisfaction on a regular basis. Such surveys could facilitate improvements through analysis of results on patient satisfaction.